Contractual Protection of Trade Secrets: An Analytical Study - Fatima Khalid Al-Harbi (International Journal of Law Research and Studies, 2026)
This research aims to study the contractual protection of trade secrets in the Saudi legal system, using a descriptive-analytical approach. The study is divided into two sections. The first section addresses the nature of trade secrets by defining them in both legislation and legal jurisprudence, and then examines the conditions necessary for their protection. The second section explores the protection of trade secrets within the framework of contractual relationships, specifically within employment contracts and licensing agreements, through non-disclosure and non-compete agreements. The study reached several conclusions, the most important of which are: For a trade secret to be granted legal protection under the Saudi legal system, three conditions must be met: the information must be confidential in its final form; it must possess commercial value due to its confidentiality; and the rights holder must take the necessary and reasonable measures to maintain its confidentiality. Furthermore, the Saudi legislator refrained from protecting secrets that violate Islamic law or public morals. While the Saudi legislator did not regulate contracts that involve trade secrets, it did stipulate liability for breaching any contractual obligation related to confidentiality.